Evaluating the e-permit system in construction using stakeholder analysis and network theory - Amer, Layal; Thneibat, Mujahed; Sammour, Farouq; Lepkova, Natalija (Journal of Civil Engineering and Management, 2025)
Electronic building permit systems, integral to e-government services, aim to enhance the efficiency and user experience of the permit process. Despite their widespread adoption, these systems often fall short, complicating and delaying the process. The presence of a variety of stakeholders in such permit systems complicates interactions between actors; nevertheless, no research has examined permit systems from a stakeholder analysis approach. This gap is filled by a formal social network analysis that thoroughly investigates interconnected and multi-level governing systems. This study investigates the electronic building permit system’s successes and failures in the construction industry. A mixed-methods approach was used, including interviews with applicants and employees, process mining analysis of event logs from 50 projects, case study observation, and social network analysis. The findings highlight significant barriers: poor communication and coordination among different agency employees, and a lack of adherence to established timeframes. Additionally, the study reveals that these systems are largely automated versions of their traditional counterparts, lacking substantial redesign or restructuring. Consequently, the researchers recommend a thorough re-evaluation and redesign of the electronic building permit system and propose implementing a one-stop-shop platform to facilitate inter-agency collaboration and streamline both internal and external communications and coordination.